The english juvenile detention centre: A lesson for the U.S.A.? - Hirschel, J. David (American journal of criminal justice, 1979)
It is important when contemplating change in the criminal justice system to survey and build upon experience both at home and overseas. In this age of increasing concern with the criminal activity of our youth it has become fashionable in some quarters to adopt a tougher attitude toward delinquent youth. This is manifested by a desire to hold juveniles directly responsible for criminal behavior and to subject them to more punitive sentencing dispositions. In this political climate it might be wise to examine the history of the English juvenile Detention Centre, with its emphasis upon providing a “short, sharp shock” for juveniles who are sent there. This article examines the philosophical rationale behind the Detention Centre regime and traces its development from establishment in 1948 to the present day. The evidence available suggests that the Detention Centre program, established to provide a strict deterrent regime for the relatively unsophisticated and not seriously delinquent offender, has not met with resounding success. Additionally, the program is shown to have departed considerably from its original standards of rigor. Indeed, it is now uncertain whether the Detention Centre differs appreciably from other English juvenile correctional institutions, and the governmental trend of thought has been toward abolition of the centres altogether. The article concludes that it may be preferable to make greater use of non-institutional dispositions than to sentence delinquent youth to short periods of incarceration.